Kenya : Poverty Reduction Strategy Annual Progress Report; 2003/2004. (IMF Staff Country Reports; Country Report ;, 2007)
Kenya's Poverty Reduction Strategy Annual progress report highlights that sound macroeconomic management policies are finally beginning to yield results in terms of macroeconomic growth, which is the underpinning for future poverty reduction. A high degree of price stability has been maintained, and real interest rates brought to historically low levels are encouraging accelerated bank lending for domestic investment. The public sector has been kept on a fiscally sustainable course. In terms of infrastructure, progress has been made in all subsectors on development of the regulatory framework.